Arvicanthis : of climates and humans during the Pleistocene and the Holocene in Africa - (:unkn) unknown (My University, 2022)
Fossil rodents are good markers of climate and landscape changes, but also of human population movements and anthropisation of the environment. During Quaternary climatic variations, North Africa experienced different waves of dispersal of animals from sub-Saharan Africa during wetter periods allowing the vegetation of the Sahara and the passage of fauna and humans. Arvicanthis, a rodent that now lives in the sub-Saharan savannahs, made occasional incursions into North Africa and the Near East at key periods in human history. The ArviClim Project "Arvicanthis: of climates and humans during the Pleistocene and the Holocene in Africa" aims to revise the fossil remains of Arvicanthis from various North African sites in order to clarify their specific attribution, their ecology, their relationship with current populations, to deduce hypotheses on their area of origin and to propose avenues of reflection on faunal and human dispersal events. We present here the first results of this project.
Keywords: African Research